The Role of Compliance in Cybersecurity: Strengthening the Digital Fortress - Vivek Madan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In today's digitally driven world, cybersecurity compliance is emerging as a core pillar of modern risk management. As cyber threats grow in sophistication and frequency, aligning with frameworks like GDPR, ISO/IEC 27001, HIPAA, SOC 2, and NIST 800-53 goes far beyond checking regulatory boxes. These standards represent a strategic approach to digital risk fostering operational resilience, organizational trust, and long-term excellence. This article dives into the measurable value of cybersecurity compliance, utilizing industry data, visual benchmarks, and a compliance maturity model. It also unpacks the challenges organizations face during implementation and provides a set of modern strategies to navigate them successfully. Ultimately, this paper positions compliance not just as a requirement but as a business enabler.